Sub-millimeter-Scale Growth of One-Unit-Cell-Thick Ferrimagnetic Cr 2 S 3 Nanosheets - Chu, Junwei; Zhang, Yu; Wen, Yao; Qiao, Ruixi; Wu, Chunchun; He, Peng; Yin, Lei; Cheng, Ruiqing; Wang, Feng; Wang, Zhenxing; Xiong, Jie; Li, Yanrong; et al. (Nano letters, 2019)
Two-dimensional (2D) magnetic materials provide an ideal platform for the application in spintronic devices due to their unique spin states in nanometer scale. However, recent research on the exfoliated monolayer magnetic materials suffers from the instability in ambient atmosphere, which needs extraordinary protection. Hence the controllable synthesis of 2D magnetic materials with good quality and stability should be addressed. Here we report for the first time the van der Waals (vdW) epitaxial growth of one-unit-cell-thick air-stable ferrimagnet Cr S semiconductor via a facile chemical vapor deposition method. Single crystal Cr S with the domain size reaching to 200 μm is achieved. Most importantly, we observe the as grown Cr S with a Néel temperature ( T ) of up to 120 K and a maximum saturation magnetic momentum of up to 65 μemu. As the temperature decreases, the samples show a transition from soft magnet to hard magnet with the highest coercivity of 1000 Oe. The one-unit-cell-thick Cr S devices show a p-type transfer behavior with an on/off ratio over 10 . Our work highlights Cr S monolayer as an ideal magnetic semiconductor for 2D spintronic devices. The vdW epitaxy of nonlayered magnets introduces a new route for realizing magnetism in 2D limit and provides more application potential in the 2D spintronics.